RELATIONSHIP OF PARENTING TO TEMPER TANTRUM BEHAVIOR OF CHILDREN 3-5 YEARS OLD IN PAUD MAWAR FKIP UNPATTI - Hermelina Abarua (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2020)
2019